Value at risk: teoría y aplicaciones - Johnson, Cristian (Estudios de Economía, 2016)
This article describes the Value at Risk concept, popularized during the last tenor fifteen years, presenting applications on stocks, bonds, interest and exchangerate forward contracts, and swaps. We applied asymmetric GARCH methodologiesover Chilean stock indexes to enhance our risk evaluation performance.Liquidity adjusted Value at Risk methodologies for individual and multiple assetportfolios are discussed. To conclude, we applied this methodology to evaluatethe performance in three Chilean financial institutions.